Reliabilitas Alat Ukur, Jenis-Jenis, Cara Pengukuran, dan Faktor-Faktor yang Mempengaruhinya - Rasyid, Achmad; Hartanto, Rudy; Priyanto, Catur (Lembaga Yasin AlSys, 2026)
Measurement reliability is a crucial aspect of research because it concerns the consistency and trustworthiness of measurement results, whereby a reliable instrument is able to produce stable data when used repeatedly under the same conditions. This paper discusses the concept of measurement reliability, its types, testing methods, and the factors that influence the level of reliability of research instruments. The types of reliability reviewed include response consistency reliability, composite item consistency, external reliability, and internal reliability. The reliability testing methods discussed comprise test–retest, parallel forms, split-half, Cronbach’s alpha, and inter-rater reliability. In addition, this study highlights various factors that affect reliability, such as item clarity, respondent conditions, measurement environment, number of items, time interval between measurements, and assessor quality. A sound understanding of reliability is expected to help researchers design and use instruments that are more accurate, consistent, and scientifically accountable, thereby improving the overall quality of research findings.